Composite carbon source coated lithium iron phosphate material and preparation method thereof, lithium ion battery and electric equipment

By adopting composite carbon source coating method and double-step temperature-raising sintering technology, the problem of uneven carbon coating of lithium iron phosphate material during sintering is solved, and the cycle life and electrochemical performance of the material are improved.

CN119240644APending Publication Date: 2025-01-03GUANGZHOU GREAT POWER ENERGY & TECH CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411367275.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, lithium iron phosphate material has uneven carbon coating during sintering, resulting in short material cycle life and low reaction activity.

Method used

The composite carbon source coating method is adopted, combining small molecule carbon sources and high-thermal stable carbon sources, and spray drying and double-step heating and sintering technology to ensure the uniformity and stability of carbon coating.

Benefits of technology

The uniform coating of lithium iron phosphate material is achieved, which improves the cycle life and electrochemical performance of the material, and solves the problems of poor coating and low reactivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240644A_ABST
    Figure CN119240644A_ABST
Patent Text Reader

Abstract

The invention provides a composite carbon source coated lithium iron phosphate material and a preparation method thereof, a lithium ion battery and electric equipment, and relates to the field of materials. The preparation method comprises the following steps: carrying out first mixing on iron phosphate, a lithium source, a first carbon source and a solvent, grinding to obtain slurry, and then carrying out spray drying to obtain a powder material; carrying out second mixing on the powder material and a second carbon source, and then sintering in an inert atmosphere to obtain a composite carbon source coated lithium iron phosphate material; the first carbon source comprises a small-molecule carbon source with the pyrolysis temperature not higher than 500 DEG C, and the second carbon source comprises a high-thermal-stability carbon source with the pyrolysis temperature not lower than 600 DEG C. According to the preparation method of the composite carbon source-coated lithium iron phosphate material provided by the invention, uniform coating of the lithium iron phosphate material is realized through cooperation of the first carbon source and the second carbon source, and the problem that the lithium iron phosphate cannot be uniformly coated by an existing carbon coating scheme after fusion-growth of the lithium iron phosphate is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of materials, and in particular to a composite carbon source-coated lithium iron phosphate material and a preparation method thereof, a lithium-ion battery and electrical equipment. Background Art

[0002] Lithium iron phosphate (LiFePO4) has significant advantages: 1) Excellent safety performance: Lithium iron phosphate material provides high safety and long cycle life due to its stable olivine structure and strong PO covalent bond. 2) Environmentally friendly: The raw material source is extensive and environmentally friendly, and does not contain precious elements such as cobalt, reducing dependence on rare resources and environmental impact. 3) Wide range of applications: It is not only suitable for power batteries of new energy vehicles, but also widely used in energy storage equipment and other fields, and demand continues to grow.

[0003] Carbon sources play a key role in the production and performance improvement of lithium iron phosphate (LiFePO4) cathode materials. They can improve the conductivity of lithium iron phosphate materials, maintain interface stability, and improve the cycling performance of materials. The uniformity of carbon coating is crucial to the performance of lithium iron phosphate materials.

[0004] Existing technical solutions generally use glucose, sucrose, and polyethylene glycol as carbon sources. During the sintering process, glucose is gradually carbonized and coated on the surface of lithium iron phosphate particles by solid phase diffusion. However, lithium iron phosphate particles will undergo a fusion-growth process during this process. It is difficult to ensure that carbon materials can be coated on the surface of fused and grown lithium iron phosphate particles by relying solely on solid phase diffusion. Lithium iron phosphate without carbon layer coating faces problems such as severe interface side reactions and short cycle life. Summary of the invention

[0005] The purpose of this application is to provide a composite carbon source coated lithium iron phosphate material and its preparation method, lithium ion battery and electrical equipment to solve the above problems.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] A method for preparing a composite carbon source coated lithium iron phosphate material, comprising:

[0008] The iron phosphate, the lithium source, the first carbon source and the solvent are first mixed and ground to obtain a slurry, and then spray-dried to obtain a powder material;

[0009] The powder material and the second carbon source are mixed for a second time, and then sintered in an inert atmosphere to obtain the composite carbon source-coated lithium iron phosphate material;

[0010] The first carbon source comprises a small molecule carbon source with a pyrolysis temperature not higher than 500°C, and the second carbon source comprises a high thermal stability carbon source with a pyrolysis temperature not lower than 600°C.

[0011] Preferably, the first carbon source comprises glucose and / or sucrose, and the second carbon source comprises long-chain alkanes and / or condensed-ring aromatic hydrocarbons;

[0012] The chemical formula of the long chain alkane is C m H 2m+2 , where m is any positive integer between 20 and 22;

[0013] The chemical formula of the condensed aromatic hydrocarbon is C 4n+2 H 2n+4 , where n≥4.

[0014] Preferably, the preparation method of the composite carbon source coated lithium iron phosphate material meets one or more of the following conditions:

[0015] (1) The lithium source includes lithium carbonate and / or lithium hydroxide;

[0016] (2) The solvent includes water;

[0017] (3) The grinding is performed using a sand mill, the grinding medium is a zirconium ball, the diameter of the zirconium ball is 0.1-0.8 mm, and the grinding time is 0.5-2 h;

[0018] (4) The mass ratio of the iron phosphate, the lithium source, and the first carbon source is 1:(0.4-0.6):(0.05-0.2).

[0019] Preferably, the inlet temperature of the spray drying is 120-150°C, and the outlet temperature is 100-120°C.

[0020] Preferably, the mass ratio of the powder material to the second carbon source is 1:(0.01-0.1).

[0021] Preferably, the second mixing is carried out by using a double planetary mixer with an orbital speed of 10-40 rpm for 2-4 hours.

[0022] Preferably, the sintering comprises:

[0023] Keep at 500-550℃ for 1-2h, then keep at 600-650℃ for 1-2h, and then keep at 750-800℃ for 2-4h;

[0024] The heating rate of the sintering is 2-5°C / min.

[0025] The present application also provides a composite carbon source coated lithium iron phosphate material, which is prepared using the preparation method of the composite carbon source coated lithium iron phosphate material.

[0026] The present application also provides a lithium-ion battery, the raw materials of which include the composite carbon source-coated lithium iron phosphate material.

[0027] The present application also provides an electrical device, including the lithium-ion battery.

[0028] Compared with the prior art, the beneficial effects of this application include:

[0029] The present application provides a method for preparing a composite carbon source coated lithium iron phosphate material, wherein the composite carbon source is composed of two types of materials, one of which is a small molecule carbon source, which serves as the main material for carbon coating; and the other is a high thermal stability carbon source, which serves to carbon-coat the fused-grown lithium iron phosphate material through a liquid diffusion process. The two types of materials play their respective advantages, and the formation of a composite carbon source can solve the problem of poor carbon coating uniformity in the existing technical solution; through the cooperation of the first carbon source and the second carbon source, the lithium iron phosphate material is uniformly coated, solving the problem that the existing carbon coating solution cannot uniformly coat the lithium iron phosphate after fusion-growth. The mechanism is as follows: by introducing a second carbon source with a high boiling point and a high pyrolysis temperature, the second carbon source can rely on its own fluidity to continuously coat the lithium iron phosphate particles with carbon after the first carbon source is pyrolyzed and during the fusion-growth process of the lithium iron phosphate by virtue of its high boiling point characteristics, and achieve the effect of uniform coating; relying on its high decomposition temperature characteristics, even after the lithium iron phosphate particles are fused and grown, they can still be uniformly coated through the pyrolysis process to ensure that the surface of the fused and grown lithium iron phosphate particles is still coated with a carbon layer, thus solving the problems of poor coating of the fused and grown lithium iron phosphate particles and the resulting low reaction activity and short cycle life in the existing technical solutions. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0031] Figure 1 This is a TEM photo of the composite carbon-coated lithium iron phosphate material obtained in Example 1;

[0032] Figure 2 This is a SEM photo of the composite carbon-coated lithium iron phosphate material obtained in Example 2;

[0033] Figure 3 This is a SEM photograph of the composite carbon-coated lithium iron phosphate material obtained in Comparative Example 5. DETAILED DESCRIPTION

[0034] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0035] A method for preparing a composite carbon source coated lithium iron phosphate material, comprising:

[0036] The iron phosphate, the lithium source, the first carbon source and the solvent are first mixed and ground to obtain a slurry, and then spray-dried to obtain a powder material;

[0037] The powder material and the second carbon source are mixed for a second time, and then sintered in an inert atmosphere to obtain the composite carbon source-coated lithium iron phosphate material;

[0038] The first carbon source comprises a small molecule carbon source with a pyrolysis temperature not higher than 500°C, and the second carbon source comprises a high thermal stability carbon source with a pyrolysis temperature not lower than 600°C.

[0039] The second carbon source has a high pyrolysis temperature (≥600°C) and a high boiling point (≥450°C). Therefore, after the thermal decomposition of the first carbon source is completed, the second carbon source can still maintain a liquid state, provide good diffusion ability, and achieve uniform coating of the lithium iron phosphate particles.

[0040] In an optional embodiment, the first carbon source includes glucose and / or sucrose, and the second carbon source includes long-chain alkanes and / or condensed-ring aromatic hydrocarbons;

[0041] The chemical formula of the long chain alkane is C m H 2m+2 , where m is any positive integer between 20 and 22;

[0042] m can be 20, 21 or 22;

[0043] The chemical formula of the condensed aromatic hydrocarbon is C 4n+2 H 2n+4 , where n≥4.

[0044] n can be any positive integer greater than or equal to 4, such as 4, 5, 6, 7, etc.

[0045] The long chain alkane may be, for example, n-eicosane, n-heneicosane or n-docosane. The condensed ring aromatic hydrocarbon may be, for example, tetracene. Pentacene or hexacene

[0046] In an optional embodiment, the preparation method of the composite carbon source coated lithium iron phosphate material meets one or more of the following conditions:

[0047] (1) The lithium source includes lithium carbonate and / or lithium hydroxide;

[0048] (2) The solvent includes water;

[0049] (3) The grinding is performed using a sand mill, the grinding medium is a zirconium ball, the diameter of the zirconium ball is 0.1-0.8 mm, and the grinding time is 0.5-2 h;

[0050] Optionally, the diameter of the zirconium ball can be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm or any value between 0.1-0.8 mm, and the grinding time can be 0.5 h, 1 h, 1.5 h, 2 h or any value between 0.5-2 h;

[0051] (4) The mass ratio of the iron phosphate, the lithium source, and the first carbon source is 1:(0.4-0.6):(0.05-0.2).

[0052] Optionally, the mass ratio of the iron phosphate, the lithium source and the first carbon source can be any value between 1:0.4:0.05, 1:0.5:0.1, 1:0.6:0.2 or 1:(0.4-0.6):(0.05-0.2).

[0053] In an optional embodiment, the inlet temperature of the spray drying is 120-150°C, and the outlet temperature is 100-120°C.

[0054] In an optional embodiment, the mass ratio of the powder material to the second carbon source is 1:(0.01-0.1).

[0055] Optionally, the mass ratio of the powder material to the second carbon source can be 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1 or any value between 1:(0.01-0.1).

[0056] In an optional embodiment, the second mixing is carried out by using a double planetary mixer with an orbital speed of 10-40 rpm (without self-rotation) for 2-4 hours.

[0057] Optionally, the rotation speed may be 10 rpm, 20 rpm, 30 rpm, 40 rpm or any value between 10-40 rpm, and the time may be 2 h, 3 h, 4 h or any value between 2-4 h.

[0058] In an optional embodiment, the sintering includes:

[0059] Keep at 500-550℃ for 1-2h, then keep at 600-650℃ for 1-2h, and then keep at 750-800℃ for 2-4h;

[0060] The heating rate of the sintering is 2-5°C / min.

[0061] Optionally, the sintering process includes: first keeping warm at 500℃, 510℃, 520℃, 530℃, 540℃, 550℃ or any value of 500-550℃ for 1-2h, then keeping warm at 600℃, 610℃, 620℃, 630℃, 640℃, 650℃ or any value of 600-650℃ for 1-2h, and then keeping warm at 750℃, 760℃, 770℃, 780℃, 790℃, 800℃ or any value of 750-800℃ for 2-4h; the sintering heating rate can be 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min or any value between 2-5℃ / min.

[0062] Keeping the temperature at 500-550°C can ensure that the first carbon source can be fully pyrolyzed and carbonized. The pyrolysis process of the first carbon source will release gases (such as CO / H2O), which may remain in the second carbon source, resulting in defects in the coating process of the second carbon source. Through a proper heat preservation process, it can be ensured that the first carbon source can be fully carbonized, reducing the interference of the pyrolysis process of the first carbon source on the second carbon source.

[0063] Keeping the temperature at 600-650° C. can provide sufficient buffer time for the second carbon source to diffuse and coat the lithium iron phosphate particles, ensuring that the second carbon source can be coated on the surface of the fused and grown lithium iron phosphate particles.

[0064] Keeping the temperature at 750-800°C can improve the graphitization degree of the first carbon source and the second carbon source, reduce the defect degree, improve the electronic conductivity, and thus improve the electrochemical performance of the material.

[0065] The material sintering process adopts a step-by-step heating process, and the coating effect of the second carbon source is enhanced by controlling the insulation time.

[0066] It should be noted that the sintering is carried out under an inert atmosphere, and the pressure of the sintering container is generally controlled at 120-150 KPa to ensure normal coating of the carbon source during sintering.

[0067] The present application also provides a composite carbon source coated lithium iron phosphate material, which is prepared using the preparation method of the composite carbon source coated lithium iron phosphate material.

[0068] The present application also provides a lithium-ion battery, the raw materials of which include the composite carbon source-coated lithium iron phosphate material.

[0069] The present application also provides an electrical device, including the lithium-ion battery.

[0070] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0071] Example 1

[0072] This embodiment provides a composite carbon source coated lithium iron phosphate material, and the preparation method thereof is as follows:

[0073] 1) Raw material mixing

[0074] Iron phosphate, lithium source and first carbon source are added to a sand mill in a mass ratio of 1:0.4:0.05, and a solvent and zirconium balls are added for grinding; the lithium source is lithium carbonate (Li2CO3); the sand milling time is 0.5 hours; the size of the zirconium ball used in the sand mill is 0.1 mm. The first carbon source is glucose, and the solvent is water.

[0075] 2) Spray drying

[0076] The slurry obtained in step 1) was dried using a spray dryer (inlet temperature was 120° C., outlet temperature was 100° C.) to obtain a dry powder material.

[0077] 3) Mixing the second carbon source

[0078] The powder material obtained in step 2) and the second carbon source were added into a double planetary mixer at a mass ratio of 1:0.01 and stirred for 2 hours at a speed of 10 rpm; the second carbon source was a long-chain alkane C 20 H 22 (n-eicosane);

[0079] 4) Finished product sintering

[0080] The sample obtained in step 3) was transferred to a sagger and subjected to a sintering process under an inert atmosphere (helium, 150Kpa) to obtain a lithium iron phosphate material. The sintering process adopted a gradient temperature increase strategy, with a temperature of 500 degrees Celsius for 1 hour, 600 degrees Celsius for 1 hour, and 800 degrees Celsius for 2 hours; the heating rate was 2°C / min.

[0081] The TEM image of the obtained composite carbon-coated lithium iron phosphate material is shown in Figure 1 shown.

[0082] Example 2

[0083] This embodiment provides a composite carbon source coated lithium iron phosphate material, and the preparation method thereof is as follows:

[0084] 1) Raw material mixing

[0085] Iron phosphate, lithium source and first carbon source are added to a sand mill in a mass ratio of 1:0.5:0.1, and a solvent and zirconium balls are added for grinding; the lithium source is lithium hydroxide (LiOH); the sand milling time is 1 hour; the size of the zirconium ball used in the sand mill is 0.45 mm. The first carbon source is sucrose, and the solvent is water.

[0086] 2) Spray drying

[0087] The slurry obtained in step 1) was dried using a spray dryer (inlet temperature was 150° C., outlet temperature was 120° C.) to obtain a dry powder material.

[0088] 3) Mixing the second carbon source

[0089] The powder material obtained in step 2) and the second carbon source were added into a double planetary mixer at a mass ratio of 1:0.05 and stirred for 3 hours at a speed of 200 rpm; the second carbon source was condensed aromatic hydrocarbon C 18 H 12

[0090] 4) Finished product sintering

[0091] The sample obtained in step 3) was transferred to a sagger and subjected to a sintering process under an inert atmosphere (helium, 150Kpa) to obtain a lithium iron phosphate material. The sintering process adopted a gradient temperature increase strategy, with a temperature of 550 degrees Celsius for 1 hour, 650 degrees Celsius for 1.5 hours, and 800 degrees Celsius for 3 hours; the heating rate was 4°C / min.

[0092] The SEM image of the obtained composite carbon-coated lithium iron phosphate material is shown in Figure 2 shown.

[0093] Example 3

[0094] This embodiment provides a composite carbon source coated lithium iron phosphate material, and the preparation method thereof is as follows:

[0095] 1) Raw material mixing

[0096] Iron phosphate, lithium source and first carbon source are added to a sand mill in a mass ratio of 1:0.6:0.2, and a solvent and zirconium balls are added for grinding; the lithium source is lithium carbonate (Li2CO3); the sand milling time is 0.5 hours; the size of the zirconium ball used in the sand mill is 0.8 mm. The first carbon source is glucose, and the solvent is water.

[0097] 2) Spray drying

[0098] The slurry obtained in step 1) was dried using a spray dryer (inlet temperature was 140° C., outlet temperature was 110° C.) to obtain a dry powder material.

[0099] 3) Mixing the second carbon source

[0100] The powder material obtained in step 2) and the second carbon source were added into a double planetary mixer at a mass ratio of 1:0.1 and stirred for 4 hours at a speed of 400 rpm; the second carbon source was a long-chain alkane C 22 H 46 (n-docosane);

[0101] 4) Finished product sintering

[0102] The sample obtained in step 3) was transferred to a sagger and subjected to a sintering process under an inert atmosphere (helium, 150Kpa) to obtain a lithium iron phosphate material. The sintering process adopted a gradient temperature increase strategy, with a temperature of 520 degrees Celsius for 1 hour, 630 degrees Celsius for 2 hours, and 780 degrees Celsius for 4 hours; the heating rate was 5°C / min.

[0103] Comparative Example 1

[0104] Different from Example 2, step 3) is not performed.

[0105] Comparative Example 2

[0106] Different from Example 2, steps 1) and 2) are not performed, and iron phosphate, lithium source and second carbon source are directly added into a double planetary mixer in a mass ratio of 1:0.5:0.1 and stirred and mixed for 3 hours at a speed of 200 rpm; the second carbon source is condensed aromatic hydrocarbon C 18 H 12 Then, the same step 4) as in Example 2 was performed.

[0107] Comparative Example 3

[0108] 1) Raw material mixing

[0109] Add iron phosphate, lithium source, first carbon source and second carbon source into a sand mill in a mass ratio of 1:0.5:0.1:0.08, add solvent and zirconium balls for grinding; the lithium source is lithium hydroxide (LiOH); the sand milling time is 1 hour; the size of the zirconium ball used in the sand mill is 0.45mm. The first carbon source is sucrose; the second carbon source is polycyclic aromatic hydrocarbons The solvent is water.

[0110] 2) Spray drying

[0111] The slurry obtained in step 1) is dried using a spray dryer to obtain a dry powder material.

[0112] 3) Finished product sintering

[0113] The sample obtained in step 2) is transferred to a sagger and subjected to a sintering process under inert atmosphere protection to obtain a lithium iron phosphate material. The sintering process adopts a gradient temperature increase strategy, with 1 hour at 500 degrees Celsius, 1.5 hours at 600 degrees Celsius, and 3 hours at 800 degrees Celsius; the heating rate is 4°C / min.

[0114] Comparative Example 4

[0115] 1) Raw material mixing

[0116] Add iron phosphate, lithium source and second carbon source into a sand mill in a mass ratio of 1:0.5:0.075, add solvent and zirconium balls for grinding; the lithium source is lithium hydroxide (LiOH); the second carbon source is polycyclic aromatic hydrocarbons The sanding time of the sand mill is 1 hour; the size of the zirconium ball used in the sand mill is 0.45 mm, and the sanding time is 1 hour; the solvent is water.

[0117] 2) Spray drying

[0118] The slurry obtained in step 1) is dried using a spray dryer to obtain a dry powder material.

[0119] 3) Mixing the first carbon source

[0120] The powder material obtained in step 2) and the first carbon source are added into a double planetary mixer at a mass ratio of 1:0.05 for stirring and mixing; the stirring time is 3 hours and the rotation speed is 200 rpm; the first carbon source is sucrose.

[0121] 4) Finished product sintering

[0122] The sample obtained in step 3) is transferred to a sagger and subjected to a sintering process under inert atmosphere protection to obtain a lithium iron phosphate material. The sintering process adopts a gradient temperature increase strategy, with 1 hour at 500 degrees Celsius, 1.5 hours at 600 degrees Celsius, and 3 hours at 800 degrees Celsius; the heating rate is 4°C / min.

[0123] Comparative Example 5

[0124] Different from Example 2, the mass ratio of the powder material to the second carbon source is 1:0.5.

[0125] The SEM image of the obtained composite carbon-coated lithium iron phosphate material is shown in Figure 3 shown.

[0126] Comparative Example 6-Comparative Example 8

[0127] The difference from Example 2 is that the parameters of each stage in the sintering process are changed, as shown in Table 1 below:

[0128] Table 1 Specific parameters

[0129] Sample Example 500℃ holding time 600℃ holding time 800℃ holding time Example 2 1 1.5 3 Comparative Example 6 5.5 0 0 Comparative Example 7 0 5.5 0 Comparative Example 8 0 0 5.5

[0130] The performance test data of the batteries prepared according to the above methods in various embodiments and comparative examples are shown in Table 2 below:

[0131] About battery production:

[0132] Positive electrode sheet: lithium iron phosphate: SP: PVDF = 96:2:2 mass ratio, add appropriate amount of NMP, stir to obtain homogeneous slurry, transfer the slurry to carbon-coated aluminum foil, and dry to obtain positive electrode sheet;

[0133] Negative electrode sheet: The negative electrode uses a metal lithium sheet;

[0134] Electrolyte: 1M LiPF6 dissolved in EC / DEC solvent.

[0135] Table 2 Electrochemical performance data

[0136]

[0137] It can be seen from Table 2 above:

[0138] 1. Comparative Example 1 uses a single small molecule carbon source compared to Example 2, which is an existing technology in the industry. This coating method has a poor coating effect on large particles and has limited improvement on the conductivity of the material, resulting in a 2.7 mAh / g reduction in capacity. Due to the lack of carbon layer coating on the reaction interface, side reactions are intensified during the cycle, resulting in a 5.8% decrease in capacity retention.

[0139] 2. Comparative Example 2 uses a single high thermal stability carbon source compared to Example 2. Lithium iron phosphate materials require a carbon source to provide a reducing environment during sintering, and the thermal stability of the thermally stable carbon source is relatively high, and it is difficult to provide a reducing atmosphere before 600 degrees Celsius, resulting in the inability of the iron phosphate raw material to react with the lithium source, reducing the conversion degree of lithium iron phosphate, resulting in a lower content of lithium iron phosphate in the finished product, and a discharge specific capacity of 16.6 mAh / g. Incompletely converted lithium iron phosphate byproducts will also increase side reactions in the electrochemical process, resulting in a 30.3% decrease in cycle stability.

[0140] 3. Comparative Example 3 is compared with Example 2, in which the two carbon sources are directly mixed without stepwise addition. After direct mixing, the two carbon sources are in contact with both the phosphorus source and the lithium source, but the high thermal stability carbon source is not conducive to the synthesis of lithium iron phosphate in the early stage of heating, resulting in that some materials cannot be completely converted into lithium iron phosphate, resulting in a discharge specific capacity lower by 1.9 mAh / g and a capacity retention rate reduced by 3.7%.

[0141] 4. Comparative Example 4 is compared with Example 2. The high thermal stability carbon source is mixed first, and then the small molecule carbon source is mixed. The pyrolysis temperature of the thermally stable carbon source is relatively high, and it is difficult to provide a reducing atmosphere before 600 degrees Celsius, resulting in the inability of the iron phosphate raw material to react with the lithium source. This operation will cause some materials to not be completely converted into lithium iron phosphate, resulting in a discharge specific capacity of 15.8 mAh / g lower and a capacity retention rate of 27.2%.

[0142] 5. The amount of high thermally stable carbon source used in Comparative Example 5 is too large compared to Example 2. Figure 3 As shown in the figure, the carbon content in the synthesized lithium iron phosphate is too high, and the SEM photo shows obvious free carbon, the amount of active components is reduced, and the discharge specific capacity is reduced by 1.4 mAh / g. In addition, the high carbon content aggravates the interface side reaction, resulting in a poor cycle life of the battery cell and a 25.7% reduction in capacity retention.

[0143] 6. Comparative Examples 6 and 7 both use fixed temperature heating, and no gradient heating process is performed. The heating temperature of Comparative Example 6 is only 500 degrees Celsius. At this temperature, the lithium iron phosphate is not completely generated and the carbon source is not fully carbonized. The battery capacity is only 5mAh / g, which is difficult to operate normally. The heating temperature of Comparative Example 7 is 600 degrees Celsius. It has the same problem as Comparative Example 6, but the sintering temperature is high, so the situation is alleviated, so the capacity is 10.3mAh / g, and it is also unable to operate stably.

[0144] 7. Comparative Example 8 uses a fixed temperature of 800 degrees Celsius for sintering compared to Example 2. Compared with the gradient heating process, the decomposition and gas production of the first carbon source will interfere with the coating process of the second carbon source, and the coating effect of the second carbon source will deteriorate. The discharge specific capacity is reduced by 0.8 mAh / g, and the capacity retention rate is reduced by 5.7%.

[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a composite carbon source coated lithium iron phosphate material, characterized in that: include: The iron phosphate, the lithium source, the first carbon source and the solvent are first mixed and ground to obtain a slurry, and then spray-dried to obtain a powder material; The powder material and the second carbon source are mixed for a second time, and then sintered in an inert atmosphere to obtain the composite carbon source-coated lithium iron phosphate material; The first carbon source comprises a small molecule carbon source with a pyrolysis temperature not higher than 500°C, and the second carbon source comprises a high thermal stability carbon source with a pyrolysis temperature not lower than 600°C.

2. The method for preparing the composite carbon source coated lithium iron phosphate material according to claim 1, characterized in that: The first carbon source includes glucose and / or sucrose, and the second carbon source includes long-chain alkanes and / or condensed-ring aromatic hydrocarbons; The chemical formula of the long chain alkane is C m H 2m+2 , where m is any positive integer between 20 and 22; The chemical formula of the condensed aromatic hydrocarbon is C 4n+2 H 2n+4 , where n≥4.

3. The method for preparing the composite carbon source coated lithium iron phosphate material according to claim 1, characterized in that: One or more of the following conditions are met: (1) The lithium source includes lithium carbonate and / or lithium hydroxide; (2) The solvent includes water; (3) The grinding is performed using a sand mill, the grinding medium is a zirconium ball, the diameter of the zirconium ball is 0.1-0.8 mm, and the grinding time is 0.5-2 h; (4) The mass ratio of the iron phosphate, the lithium source, and the first carbon source is 1:(0.4-0.6):(0.05-0.2).

4. The method for preparing the composite carbon source coated lithium iron phosphate material according to claim 1, characterized in that: The inlet temperature of the spray drying is 120-150°C, and the outlet temperature is 100-120°C.

5. The method for preparing the composite carbon source coated lithium iron phosphate material according to claim 1, characterized in that: The mass ratio of the powder material to the second carbon source is 1:(0.01-0.1).

6. The method for preparing the composite carbon source coated lithium iron phosphate material according to claim 1, characterized in that: The second mixing is carried out by using a double planetary mixer with an orbital speed of 10-40 rpm for 2-4 hours.

7. The method for preparing the composite carbon source coated lithium iron phosphate material according to any one of claims 1 to 6, characterized in that: The sintering comprises: Keep at 500-550℃ for 1-2h, then keep at 600-650℃ for 1-2h, and then keep at 750-800℃ for 2-4h; The heating rate of the sintering is 2-5°C / min.

8. A composite carbon source coated lithium iron phosphate material, characterized in that: The material is prepared by the method for preparing the composite carbon source coated lithium iron phosphate material according to any one of claims 1 to 7.

9. A lithium ion battery, characterized in that: The raw material includes the composite carbon source coated lithium iron phosphate material as described in claim 8.

10. An electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Cited By

  • Self-adjusting expansion lithium iron phosphate material and preparation method thereof, lithium ion battery and electric equipment

    CN121202100A

  • Preparation method of phosphate-based positive electrode material and phosphate-based positive electrode material

    CN121553919A

  • Preparation methods of phosphate-based cathode materials and phosphate-based cathode materials

    CN121553919B

  • Preparation method of gradient composite coated lithium iron phosphate material

    CN121651314A